ADVANCEMENTS IN LIPID-BASED NANOTHERANOSTICS FOR MANAGING ATHEROSCLERO-SIS: A REVIEW - DHORAI, MANIGANDAN; NIZAM, IMRANKHAN; ASAITHAMBI, KALAISLEVI; KUPPUSAMY, GOWTHAMARJAN (International Journal of Applied Pharmaceutics, 2025)
Atherosclerosis, a complicated and chronic inflammatory disorder, is the main cause of various cardiovascular issues, including coronary heart assaults and strokes. Acute myocardial infarction and stroke can be partially prevented with current clinical measures, such as statin medications, but the risk is still very high. The concept of combinatorial therapy using both diagnosis and therapeutics through a single platform is known as theranostics. As evident from pre-clinical and clinical studies, nano-based theranostics are widely used in cancer detection and treatment. Solid lipid nanoparticles (SLNs), nanostructured lipid carriers (NLCs), and nanoliposomes are examples of synthetic/natural lipid-based delivery systems that have drawn much interest as nano-scaled drug delivery system due to their potential benefits, which include easy large-scale production, relatively low toxicity, and composition accessibility. Traditionally, for the study and evaluate the effects of therapy on atherosclerosis, x-ray angiography was used. Nevertheless, measuring the amount of stenosis brought on by plaques remains the main objective of clinical studies for atherosclerosis. Several high-risk plaque features, such as a thin fibrous cap, a big necrotic core, macrophage infiltration, neovascularization, and intraplaque bleeding, can now be investigated using cutting-edge imaging methods. This review summarises nanotheranostic for diagnosing and treating atherosclerosis and the different strategies for targeting atherosclerotic plaque.